2013
DOI: 10.1194/jlr.r035766
|View full text |Cite
|
Sign up to set email alerts
|

Needles in the genetic haystack of lipid disorders: single nucleotide polymorphisms in the microRNA regulome

Abstract: This article is available online at http://www.jlr.org inhibits protein translation. Although mammalian miRNAs were not discovered until a decade ago ( 2 ), they have rapidly emerged as important posttranscriptional regulators of gene expression in a wide variety of biological pathways ( 3 ). Moreover, miRNAs have been demonstrated to be i ) stable plasma biomarkers of physiological status ( 4,5 ), ii ) novel intercellular signaling molecules ( 6 ), iii ) etiological factors in complex diseases ( 7 ), and iv )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small regulatory RNA molecules that have been shown to be involved in a wide range of biological pathways by modulating expression of specific mRNAs [ 20 ]. The role of miRNAs in lipid metabolism has been recently demonstrated [ 21 ] and lipid homeostasis was found to be governed in part by an intricate web of miRNA activity [ 22 ]. In bovine mammary gland, the expression of numerous miRNAs was increased during the postpartum or the early lactation periods as compared to the dry period [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small regulatory RNA molecules that have been shown to be involved in a wide range of biological pathways by modulating expression of specific mRNAs [ 20 ]. The role of miRNAs in lipid metabolism has been recently demonstrated [ 21 ] and lipid homeostasis was found to be governed in part by an intricate web of miRNA activity [ 22 ]. In bovine mammary gland, the expression of numerous miRNAs was increased during the postpartum or the early lactation periods as compared to the dry period [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PolymiRTS database currently focuses on featuring polymorphisms in miRNA seed regions and miRNA target sites. Recent studies have revealed the functional importance of genetic polymorphisms in other parts of the miRNA regulome ( 46 , 47 ). Polymorphisms in pre-miRNAs, pri-miRNAs and miRNA promoters have been associated with many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This approach could be much more reproducible, given that the presence or absence of an SNP in the genes encoding an miRNA does not change whether the DNA comes from leukocytes or any other type of cell. Moreover, it is known that a single miRNA can target hundreds of mRNA transcripts for either translation repression or degradation, and the detection of a polymorphism in a gene encoding a particular miRNA can affect many mRNAs and have a great influence [ 48 , 49 ]; such as an intermediate hairpin precursor miRNA (pre-miRNA), which is transported to the cytoplasm by exportin-5 and further processed by another RNase III–like enzyme, Dicer, to the mature miRNA (for a review, see Kim, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This long pri-miRNA (having several hundred nucleotides) is further processed into an intermediate hairpin precursor miRNA (pre-miRNA). The pre-miRNAs is further processed by Dicer, to the mature miRNAs [ 30 , 48 ]. Pre-miRNA polymorphisms may have an important functional role for miRNA binding and posttranscriptional regulation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%